2020
DOI: 10.48550/arxiv.2006.09910
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parameterised post-Newtonian formalism for the effective field theory of dark energy via screened reconstructed Horndeski theories

Cyril Renevey,
Joe Kennedy,
Lucas Lombriser

Abstract: We bring together two popular formalisms which generically parameterise deviations from General Relativity on astrophysical and cosmological scales, namely the parameterised post-Newtonian (PPN) formalism and the effective field theory (EFT) of dark energy and modified gravity. These separate formalisms are successfully applied to independently perform tests of gravity in their respective regimes of applicability on vastly different length scales. Nonlinear screening mechanisms indeed make it imperative to pro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…[40] and later extended to Horndeski theories with luminal propagation of gravitational waves in Ref. [41]. One can use these results to write the correction to the metric field up to 1PN,…”
Section: Corrections To the Metric And Effective Stress-energy Tensor...mentioning
confidence: 97%
See 3 more Smart Citations
“…[40] and later extended to Horndeski theories with luminal propagation of gravitational waves in Ref. [41]. One can use these results to write the correction to the metric field up to 1PN,…”
Section: Corrections To the Metric And Effective Stress-energy Tensor...mentioning
confidence: 97%
“…Consequently, the non-linearity renders post-Newtonian approaches difficult to implement due to the linearisation of the relevant field equations. However, it was shown that this problem can be circumvented with the employment of the so-called scaling method [38][39][40][41] that enables an expansion in screened regions. More specifically, the method can be used to both identify the leading corrections from the scalar field to the metric field equations in the screened small-scale regions or conversely of the unscreened theory on large scales.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This has motivated the search for cosmological models achieving a dynamical self-tuning of the Hubble expansion rate to the small observed value, even in the presence of a large vacuum energy density; for some recent work in this direction, see [2][3][4][5][6][7][8][9]. We also refer the reader to the review [10] for a discussion of the cosmological constant problem from the EFT viewpoint, and to the literature on effective field theories of dark energy and quintessence [11][12][13][14][15][16][17] for a complementary perspective. It appears extremely hard, if not impossible, to come up with an EFT which would avoid large quantum contributions to the vacuum energy density, as in (1.4).…”
Section: Introductionmentioning
confidence: 99%